Pelaksanaan Pendidikan Kewirausahaan dalam Program Double Track pada Sekolah Menengah Atas di Kabupaten Banyuwangi - Alfiyah, Nurul; Siska, Astri Iga; Kareja, Novilia (Jurnal Pendidikan Ekonomi Undiksha, 2022)
This study focuses on the analysis of the implementation of entrepreneurship education in the double track program in Banyuwangi Regency Senior High Schools that have implemented this program, so that it is expected to be an example for other high schools. The study used descriptive qualitative methods with research subjects namely SMAN 1 Purwoharjo and SMAS 1 Muhammadiyah Banyuwangi, including school principals, entrepreneurship teachers and double track program supervisors, as well as students. Data were obtained by means of in-depth and semi-structured interviews, observations, and "focus group discussions" with colleagues. The result of this research is that the double track program is successful in accordance with its objectives, namely developing interests and talents as well as independence through entrepreneurship. The supporting factors of this program are technological advances and student enthusiasm, while the inhibiting factor is the limited facilities and infrastructure to support the success of the double track learning process.